VD_FINDINFO HC / 2017 / 269 vom 30. März 2017 - VD Tribunal cantonal (2017)
CONTRAT D'ENTREPRISE, DÉFAUT DE LA CHOSE, RÉSILIATION, DILIGENCE, OBLIGATION DE RENSEIGNER | 120 al. 1 CO, 120 al. 2 CO, 124 al. 1 CO, 365 al. 3 CO, 317 al. 1 CPC (CH)